Significados de género y sexualidad en la violencia de pareja: víctimas, agresores y policías en Hermosillo, Sonora - Espinoza Cid, Claudia Esthela; García Figueroa, Gabriela (El Colegio de México, 2018)
This article explores from a sociocultural perspective the sexual and gender meanings expressed by women suffering intimate partner violence (IPV), aggressors and municipal police officers intervening in cases of violence in Hermosillo, Sonora. This analysis is important because it helps to understand the links between these meanings (particularly those associated to gender violence) and the institutional practices of social agents directly involved in police intervention in response to this problem in that city. The study confirms the presence of traditional assessments, ideas and perceptions about the social relations between men and women, which affect the institutionalized responses of those who commit or suffer violence, as well as the practices of law enforcement officials intervening in case of violence.